2019
DOI: 10.1080/15384101.2019.1593647
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated lncRNA-UCA1 contributes to metastasis of bile duct carcinoma through regulation of miR-122/CLIC1and activation of the ERK/MAPK signaling pathway

Abstract: In the present study, we aimed to identify specific lncRNAs and miRNAs, as well as mRNAs, involved in bile duct carcinoma (BDC) and to further explore the way in which lncRNA UCA1 regulates cell metastasis ability. Differentially expressed RNAs were screened out from the TCGA database. In in vitro experiments, qRT-PCR was used to measure lncRNA UCA1, miR-122 and CLIC1 expression. We performed a dual luciferase assay to validate the target relationships among UCA1, CLIC1 and miR-122. The cell migration ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that long non-coding RNAs (lncRNAs) perform important or vital functions in the malignant tumors [9][10][11][12][13][14][15]. LncRNA urothelial cancer associated 1 (UCA1) is abnormally expressed in esophageal squamous cell carcinoma, colorectal cancer, gastric cancer melanoma cells, pancreatic cancer, thyroid cancer, lung cancer and so on [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In vitro and in vivo assays were conducted to further explore its underlying roles in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Jiao et al have found that lncRNA UCA1 is a significant molecular for tumor growth and could be an effective target for EC therapy [9]. Several articles have conveyed that lncRNA UCA1 could perform as a competing endogenous RNA (ceRNA) of some microRNA (miRNAs), such as miR-193a [7] and miR-122 [10]. miRNA-485-5p (miR-485-5p) strained EC tumorigenesis and could provide as a novel candidate for therapeutic applications in EC treatment [11].…”
Section: Introductionmentioning
confidence: 99%
“…16 The relationship between LncRNA and ERK/MAPK signaling pathway has been reported in a variety of cancers, including hepatocellular carcinoma, bile duct carcinoma and lung cancer. [17][18][19] LncRNA PICART1 inhibits cell proliferation by regulating ERK/MAPK signaling pathways in GC. 20 In addition, LncRNA CARLo-5 promotes proliferation and activates the ERK/MAPK pathway in GC.…”
Section: Introductionmentioning
confidence: 99%